La falta de tiempo en la indagación previa en los delitos de lesa humanidad y su afectación en los derechos constitucionales - Flores Jerbis, Simón Israel (2013)
This legal research aims to demonstrate that our society and punishable involved in a case are victims of adversarial criminal justice system in our country, in cases where the preliminary investigation does not determine the difference between a common crime case with another that focuses in severe cases of social unrest or major negative impact on our community, except for crimes against humanity. The Art 215 of the Criminal Procedure Code .It does not give enough time for an optimal research .This article in question does not take into account any features or forms of crime and only imposes a time toper form a preliminary investigation that all views is insufficient for thorough scientific and technical research , to clarify the crime and not even take into account the limited technical and scientific reality which is national justice which could also be a feature that could hinder the development of research, as there are many scientific tests have to be performed outside our borders or just our collaborators of justice do not handle perfectly and that is where are violated Constitutional Rights and Principles .due to time and in as many cases for lack of money to apply these skills independently , so I believe pose an urgent need to reform or expansion hoping Article described thus imposed , and the need to resolve prevails each case is presented according to their characteristics and patterns and that the time constraint is not a cause for an investigation not scientifically sound , and that fort his reason that pass- archive a rugged case that this whatever .For lack of evidence. And so with this improvement does not give way to thickening of the files that have not been resolved in our country